Effect of Alum Dose in the Coagulation Process for Decreasing the Pollutant in the Palm Oil Mill Effluent: Experimental and Kinetic Analysis - Iqbal Syaichurrozi; Jayanudin Jayanudin; Listiyani Nurwindya Sari; Anellysha Putri Apriantika (Eksergi, 2022)
Palm oil mill effluent (POME) is palm oil processing industrial waste that cannot be discharged directly into water bodies. Therefore, this waste must be treated. One method that can be used to treat it is coagulation. The purpose of this study was to investigate the effect of coagulant doses on the coagulation process for treating the POME through experimental and kinetic analysis. The alum dose was varied to 1, 3, 5, 10, 15 g/L. The volume of treated waste was 1 L. Before adding alum, the pH of POME was adjusted to 7.0 with the addition of technical grade NaOH. The coagulation process was carried out for 180 minutes at room temperature. Every 20 minutes, the pH of the liquid was measured and a fluid sample as much as ±50 mL was taken to be settled for 24 hours. Next, the total suspended solid (TSS) concentration in the supernatant was analyzed. The results showed that the addition of alum could decrease the liquid pH and increase the TSS of the liquid. The coagulation process for 180 minutes resulted in a TSS reduction efficiency of 33.3, 33.3, 37.1, 1.7, -17.8% at alum doses of 1, 3, 5, 10, 15 g/L respectively. The first-order kinetic model provided a better prediction than the second-order kinetic model with R2 values of 0.7876-0.9707 and 0.2746-0.8912, respectively.